New assay forGardnerella vaginalisloads correlates with Nugent scores and has potential in the diagnosis of bacterial vaginosis. Issue 9 (September 2015) - Cox, Ciara; McKenna, James P.; Watt, Alison P.; Coyle, Peter V.
Abstract : N/A: Gardnerella vaginalis is a Gram‐variable anaerobic bacterium present in 100 % of women with bacterial vaginosis (BV). BV is a complex polymicrobial condition with no single causative agent. The current laboratory detection method for BV relies on a Gram‐stain Nugent score to estimate the quantity of different bacterial morphotypes in the vaginal micro flora. Whilst the Nugent score can distinguish between women with and without BV, a significant proportion are categorized as intermediate, which fails to differentiate a normal from an abnormal vaginal micro flora. A singleplex G. vaginalis TaqMan real‐time quantitative PCR (qPCR) assay was developed and compared with the 'gold standard' Nugent score. Detection and quantification of G. vaginalis was performed on vaginal specimens with positive, negative and intermediate Nugent scores. The G. vaginalis qPCR assay demonstrated high analytical specificity against a broad microbial panel and analytical sensitivity down to 3.1 × 10 4 copies ml − 1 . There was a significantly higher G. vaginalis load in women with BV compared with intermediate and non‐BV women ( P value = 5.1 × 10 − 14 ). All Nugent scores in keeping with BV had qPCR loads of ≥ 10 7 copies ml − 1 . Among the 24 undefined women (11.8 %) in the study with an intermediate flora, 14 (58.3 %) had a G. vaginalis load of ≥ 10 7 copies ml − 1 . In this study a threshold of 10 7 copies ml − 1 had positive and negative predictive values of 57.1 and 100 % for BV; the high qPCR loads among the intermediate Nugent scores suggest the need for a new approach in classifying BV and the potential for qPCR to play a role.